Mad heart be brave : essays on the poetry of Agha Shahid Ali - Ali, Kazim, 1971- (University of Michigan Press, 2017)
"Agha Shahid Ali (1949-2001) published seven highly acclaimed poetry collections in his lifetime. A native of Kashmir, he was respected and beloved both in India and the United States, where he taught for two decades in writing programs at schools such as the University of Massachusetts-Amherst, the University of Utah, New York University, and Brooklyn College. Ali embraced traditional forms of Western poetry, such as the sonnet, pantoum, villanelle, Sapphic stanzas, and sestine, before innovating an approach in English to the traditional Urdu ghazal. His poetry won the praise of contemporary American masters of form like Carolyn Kizer, James Merrill, and Anthony Hacht and of poetic innovators like Michael Palmer and Donald Revell. Collectively, the twenty essays of Mad Heart Be Brave--some of which are by his former students, now highly regarded poets themselves--offer a comprehensive consideration of Ali's work as poet, teacher, translator, and thinker.There are essays that look at his embrace of traditional forms, his use of appropriation and palimpsest in his poetry, his work as a translator, his influence and approaches as a teacher, and his relationship to the poetry scenes in both India and the United States. Several pieces explore Ali's relationship to the Kashmiri conflict, the question of nationalism, and his groundbreaking collection, The Country Without a Post Office. Later essays look at the erotic content of his work as well as his innovation in poetic forms, including his work at bringing "real ghazals" (as he called them) into English. The book concludes with a retrospective piece by Amitav Ghosh and a comprehensive bibliography of Ali's published work that will be a major resource for future scholarship."--Page 4 of cover.
Keywords: Agha, Shahid Ali, -- 1949-2001.; Agha, Shahid Ali, -- 1949-2001; Ghazals -- History and criticism.; Ghazals -- Histoire et critique.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Ghazals; Criticism, interpretation, etc.